CONCEPTS AND METHODOLOGICAL PRINCIPLES FOR THE DEVELOPMENT OF FUNCTIONAL INGREDIENTS AND DAIRY PRODUCTS WITH INCREASED PROTEIN CONTENT - Ivan A. Evdokimov; Anna V. Bannikova (Вестник Северо-Кавказского федерального университета, 2022)
There was a discussion on the dairy market in Russia. It is shown that dairy products successfully have taken place in consumer preferences. A deficit of valuable protein in the diet of modern human was remarkable leading to the development of certain nutritional diseases. As part of a solution of the problem in providing the high-quality protein to the population the concept and methodological principles of the development of functional ingredients and dairy products with a high protein content were created. Scientific principles of the development of functional ingredients and products based on protein were formulated, which includes analysis of the problem on lack of protein and assessment the relevance of creating the functional dairy products and ingredients, choosing a protein source, processing in order to obtain functional ingredients and products to further incorporate an additional source of protein. The concept of the gradation of protein content was proposed in utilising the components and their interactions in functional dairy products, which also includes in addition of dietary fiber, emulsifiers and probiotics, the consumption of which is also very important in the modern food science.